Conversion of Twice‐Daily Tacrolimus to Once‐Daily Tacrolimus Formulation in Stable Pediatric Kidney Transplant Recipients: Pharmacokinetics and Efficacy. Issue 8 (4th June 2013) - Min, S. I.; Ha, J.; Kang, H. G.; Ahn, S.; Park, T.; Park, D. D.; Kim, S. M.; Hong, H. J.; Min, S. K.; Ha, I. S.; Kim, S. J.
Abstract: The pharmacokinetics, efficacy and safety of once‐daily tacrolimus formulation (Tac‐OD) were assessed in 34 stable pediatric kidney transplant recipients. Enrolled patients received their dose of twice‐daily tacrolimus formulation (Tac‐BID) on study Days 0 through 7. On the morning of study Day 8, the total daily doses for patients were converted to Tac‐OD on a 1:1 basis and maintained on a once‐daily morning dosing regimen. Tacrolimus pharmacokinetic profiles were obtained on study Days 7, 14 and 28 (after dose adjustment). Although the mean C0 concentrations (4.10 ± 1.16–3.53 ± 1.10 ng/mL, p = 0.004), and AUC0–24 (151.8 ± 41.6–129.8 ± 39.3 ng h/mL, p < 0.001) were decreased significantly after a 1:1 based conversion, there was high interindividual variability. The dose of Tac‐OD was decreased in 26.5% and increased in 44.1% of patients. The resultant tacrolimus dose and pharmacokinetic profiles on study Day 28 were comparable to those on Day 7. There were no serious adverse events. In conclusion, Tac‐BID can be safely converted to Tac‐OD in stable pediatric kidney transplant patients with the heightened therapeutic drug monitoring. Effects of drug conversion on the cardiovascular risk factors, neurological side effects and adherence should be further evaluated. Abstract : This study highlights that the conversion of twice‐daily tacrolimus to once‐daily tacrolimus formulation results in highly variable changes in pharmacokinetic parameters of tacrolimus in stable pediatric kidney transplant patients.